2014
DOI: 10.1155/2014/642527
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nanosheet Surface Structure of Titanium Alloys on Cell Differentiation

Abstract: Titanium alloys are the most frequently used dental implants partly because of the protective oxide coating that spontaneously forms on their surface. We fabricated titania nanosheet (TNS) structures on titanium surfaces by NaOH treatment to improve bone differentiation on titanium alloy implants. The cellular response to TNSs on Ti6Al4V alloy was investigated, and the ability of the modified surfaces to affect osteogenic differentiation of rat bone marrow cells and increase the success rate of titanium implan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 39 publications
1
14
0
Order By: Relevance
“…We found that the TNS on the titanium alloy surface leads to the regulation of osteogenic differentiation of bone marrow cells and enhances mineralization 5) . We then selected a heating temperature of around 600°C based on a study by Kim 7) .…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…We found that the TNS on the titanium alloy surface leads to the regulation of osteogenic differentiation of bone marrow cells and enhances mineralization 5) . We then selected a heating temperature of around 600°C based on a study by Kim 7) .…”
Section: Discussionmentioning
confidence: 81%
“…Surfaces with nanostructures are well-known to possess increased surface area compared with those without such features 5,6,16) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Coutinho 57 studied the influence of superficial treatments on titanium, and observed that anodized titanium possessed lower roughnesses and smaller contact angles than polished titanium surfaces. Komasa et al 58 demonstrated that titania (titanium oxide) nanosheetmodified titanium alloys were more hydrophilic and exhibited markedly improved wettabilities compared to unmodified titanium alloys.…”
Section: Morphology and Wettabilitymentioning
confidence: 99%